EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1961)
Abstract The article presents several problems related to accounting, which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants and were presented as the second half of the C.P.A. examination in accounting theory on May 19, 1961. Some of the questions were based on the topic of consolidated statements of any company, like, whose financial position is represented by consolidated statements; consolidated statements and beneficiaries; proper consolidated statements of companies, etc. One of the problem states that a company P had 300,000 shares of stock outstanding. It owned 75% of the outstanding stock of T. T owned 20,000 shares of P's stock. The figure of P's outstanding stocks in the consolidated balance sheet has been asked. A question has been asked that is it acceptable accounting treatment to carry investments in subsidiaries not consolidated at cost. A question focuses on the issue of the profit increment of any company, but no valid reasons in support of this growth has been presented to the president by the accountant, as everything seems as stable as it looked when the company started.